2022
DOI: 10.1371/journal.pone.0264093
|View full text |Cite
|
Sign up to set email alerts
|

Wasp venom peptide improves the proapoptotic activity of alendronate sodium in A549 lung cancer cells

Abstract: Background Lung cancer in men and women is considered the leading cause for cancer-related mortality worldwide. Anti-cancer peptides represent a potential untapped reservoir of effective cancer therapy. Methodology Box-Behnken response surface design was applied for formulating Alendronate sodium (ALS)-mastoparan peptide (MP) nanoconjugates using Design-Expert software. The optimization process aimed at minimizing the size of the prepared ALS-MP nanoconjugates. ALS-MP nanoconjugates’ particle size, encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…In addition, the highly linear correlation of the predicted versus observed size reflects the harmony between the observed and predicted values indicating the appropriateness of the model (Fahmy, Badr-Eldin et al., 2020 ). The experimental design results showed that sonication time in the current study exhibited a similar negative effect on the particle size, indicating that the particle size significantly decreases with increasing sonication time (Alhakamy et al., 2022 ). The observed reduction in size could be attributed to the main principle of the sonication process.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the highly linear correlation of the predicted versus observed size reflects the harmony between the observed and predicted values indicating the appropriateness of the model (Fahmy, Badr-Eldin et al., 2020 ). The experimental design results showed that sonication time in the current study exhibited a similar negative effect on the particle size, indicating that the particle size significantly decreases with increasing sonication time (Alhakamy et al., 2022 ). The observed reduction in size could be attributed to the main principle of the sonication process.…”
Section: Discussionsupporting
confidence: 53%
“…The results showed a lower IC 50 value (1.3 ± 0.34 µM) compared to ALS (IC 50 37.6 ± 1.79 µM). Moreover, after treatment with the ALS-MP nanoconjugates, a higher percentage of cells in the G2-M phase was noted during cell cycle analysis [30]. Cisplatin is used as a standard and effective drug in lung cancer chemotherapy.…”
Section: Effect Of Peptides On Lung Cancer Cellsmentioning
confidence: 99%